2015
DOI: 10.1111/sms.12549
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen intake increases exercise time to exhaustion: A possible role for preventing exercise‐induced fatigue

Abstract: Although the intake of nonsteroidal anti-inflammatory drugs (NSAIDs) intake by athletes prevents soreness, little is known concerning their role in exercise performance. This study assessed the effects of ibuprofen intake on an exhaustive protocol test after 6 weeks of swimming training in rats. Animals were divided into sedentary and training groups. After training, animals were subdivided into two subsets: saline or ibuprofen. Afterwards, three repeated swimming bouts were performed by the groups. Ibuprofen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…These findings suggested that exercise performance was, at least in part, regulated by pain perception, and hence, paracetamol could improve exercise performance through increased pain tolerance and lower perceived exertion. This is also supported by animal data showing that ibuprofen improved swimming performance (time to exhaustion) in rats, plausibly through reduced susceptibility to exercise‐induced fatigue …”
Section: Exercise Performancesupporting
confidence: 59%
See 1 more Smart Citation
“…These findings suggested that exercise performance was, at least in part, regulated by pain perception, and hence, paracetamol could improve exercise performance through increased pain tolerance and lower perceived exertion. This is also supported by animal data showing that ibuprofen improved swimming performance (time to exhaustion) in rats, plausibly through reduced susceptibility to exercise‐induced fatigue …”
Section: Exercise Performancesupporting
confidence: 59%
“…This is also supported by animal data showing that ibuprofen improved swimming performance (time to exhaustion) in rats, plausibly through reduced susceptibility to exercise-induced fatigue. 20 In a follow-up study to the cycle time trial, the same group sought to determine whether paracetamol could also improve exercise capacity in the heat. 21 The background to this hypothesis comes from the fact that paracetamol has antipyretic effects for fever management, and perhaps also in afebrile patients.…”
Section: What Is New?mentioning
confidence: 99%
“…Once those peripheral nociceptors are sensitized (hyperalgesia), innocuous tactile stimuli, such as allodynia, are felt in other distal parts of the body innervated by the same sensory neuron or branches of the main neuron [22,26]. Thus, considering that the nociceptive process radiates to other distal areas of the body, we decided to evaluate the nociception of animals using von Frey filaments, which is one of the most used tools for this determination in animal models [13,33,45,52]. Moreover, the present protocol also induced strength decreases at 3, 12, 48 and 72 h post-exercise.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found a similar effect following ibuprofen administration. 23 As already reported, diclofenac treatment interferes in the synthesis of inflammatory markers in different organs, including the liver. 30 The production of these molecules is mediated by nuclear transcription factors, which, in turn, might be activated by these cytokines in a physiological feedforward.…”
Section: F I G U R E 3 Effects Of Exercise Boutsmentioning
confidence: 81%
“…Diclofenac was administered for nine days (10 mg/kg daily) and removed 24 hours before the last exhaustive bout because there is no evidence about side effect, and this period would not be enough to stop a possible therapeutic effect. 23 Interestingly, pre-treatment with diclofenac proved effective in increasing the time to exhaustion, which has not yet been demonstrated in humans. 15 This may occur due to differences in muscle glycogen that has a more central role in glucose homeostasis in humans (threefold to eightfold more muscle glycogen than liver glycogen when compared to mice).…”
Section: Discussionmentioning
confidence: 99%